Industry Partnership: Lab on Chip Chemical Sensor Technology for Ocean Observing - Mowlem, Matt; Beaton, Alexander; Pascal, Robin; Schaap, Allison; Loucaides, Socratis; Monk, Sam; Morris, Andrew; Cardwell, Christopher L.; Fowell, Sara E.; Patey, Matthew D.; López-García, Patricia (Frontiers in Marine Science, 2021)
We introduce for the first time a new product line able to make high accuracy measurements of a number of water chemistry parameters in situ: i.e., submerged in the environment including in the deep sea (to 6,000 m). This product is based on the developments of in situ lab on chip technology at the National Oceanography Centre (NOC), and the University of Southampton and is produced under license by Clearwater Sensors Ltd., a start-up and industrial partner in bringing this technology to global availability and further developing its potential. The technology has already been deployed by the NOC, and with their partners worldwide over 200 times including to depths of ∼4,800 m, in turbid estuaries and rivers, and for up to a year in seasonally ice-covered regions of the arctic. The technology is capable of making accurate determinations of chemical and biological parameters that require reagents and which produce an electrical, absorbance, fluorescence, or luminescence signal. As such it is suitable for a wide range of environmental measurements. Whilst further parameters are in development across this partnership, Nitrate, Nitrite, Phosphate, Silicate, Iron, and pH sensors are currently available commercially. Theses sensors use microfluidics and optics combined in an optofluidic chip with electromechanical valves and pumps mounted upon it to mix water samples with reagents and measure the optical response. An overview of the sensors and the underlying components and technologies is given together with examples of deployments and integrations with observing platforms such as gliders, autonomous underwater vehicles and moorings.